Applying Precision Medicine and Immunotherapy Advances from Oncology to Host-Directed Therapies for Infectious Diseases - Mahon, Robert N.; Hafner, Richard (Frontiers in Immunology, 2017)
To meet the challenges of increasing antimicrobial resistance, the infectious disease community needs innovative therapeutics. Precision medicine and immunotherapy are transforming cancer therapeutics by targeting the regulatory signaling pathways that are involved not only in malignancies, but also in the metabolic and immunologic function of the tumor microenvironment. Infectious diseases target many of the same regulatory pathways as they modulate host metabolic functions for their own nutritional requirements, and impede host immunity. These similarities and the advances made in precision medicine and immuno-oncology that are relevant for the current development of host-directed therapeutics (HDTs) to treat infectious diseases are discussed. To harness this potential, improvements in drug screening methods and development of assays that utilize the research tools including high through-put multiplexes already developed by oncology are essential. A multi-disciplinary approach that brings together immunologists, infectious disease specialists, and oncologists will be necessary to fully develop the potential of HDTs.